Negotiating Conflict, The Need Analysis of Developing Digital-Based English Teaching Materials for Midwifery Students - Nuranisa, Nisa; Gailea, Nurhaeda; Juniardi, Yudi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the need of midwifery students for developing digital based English for midwifery teaching materials. The data collection technique used was a questionnaire to analyze the needs for developing digital teaching materials which was developed based on analysis indicators at the ADDIE development model stage. The questionnaire was analyzed using descriptive analysis based on the results from respondents which included (a) learner characteristics (b)resources analysis, and (c)learning objectives. Based on the results of the needs analysis, it was found that the analysis of learner characteristics showed that 87.03% of students had knowledge of the use of digital teaching materials in learning, 94.44% of students had a positive view of the use of digital teaching materials in learning, 100% of students had the habit of using digital resources in daily life, 100% of students have an interest in using digital teaching materials in learning, and 94.44% have an interest in digital teaching materials to foster learning independence. Meanwhile, the results of resource analysis show that 87.03% of students know that the substance of teaching material content is available in journals, books and sources related to lecture material, 100% of students have laptops/gadgets that can support the use of digital teaching materials, and 100% of students have an understanding of the use of digital technology in learning. Meanwhile the result of the learning objectives showed that in general students have a tendency to be interested in digital teaching materials.